Design and analysis of a six degrees of freedom serial–parallel robotic mechanism with multi-degree of freedom legs. (28th November 2018) - Zhang, Ziwei; Meng, Guoying
A novel mobile serial–parallel mechanism with legs for in-pipe use is proposed. The mobile robotic mechanism is composed of two identical three-universal joint–prismatic joint–universal joint parallel mechanisms connected in series and two gripping modules. The proposed parallel mechanism has two rotational freedoms and one translational freedom. In addition, the parallel mechanism can achieve continuous and equivalent rotation. The singularities of the parallel mechanism are analyzed. The overall serial–parallel mechanism has six degrees of freedom, and each gripping module has four degrees of freedom. Each parallel mechanism in the waist module is driven by three servo-electric cylinders and each leg mechanism in the gripping modules is controlled by a linear actuator. The robotic mechanism can perform peristaltic movement and turning in space. The robotic mechanism possesses a simple structure and high flexibility, along with the merits of serial–parallel mechanism. In this article, analytic models for the kinematics and dynamics of the robotic mechanism are derived. Additionally, numerical examples are given, and their solutions are validated based on results obtained by SimMechanics and Adams.